Pedicled buccal fat pad graft for root coverage in severe gingival recession defect - Saurav Panda; Massimo Del Fabbro; Anurag Satpathy; Abhaya Chandra Das (Wolters Kluwer Medknow Publications, 2016)
Gingival recession (GR) is a condition resulting in root exposure which leads to root sensitivity, pain, root caries, plaque retention, poor esthetics, and tooth loss. Sites exhibiting Miller Class III and IV GR are not suitable for treatment with surgical root coverage techniques, and their prognosis are very poor with current techniques. In this case report, pedicled buccal fat pad (PBFP) was employed as subepithelial graft technique for root coverage of maxillary tooth with Class III GR defect along with furcation involvement and the absence of keratinized gingiva. PBFP as the subepithelial graft is likely to increase the predictability and outcome of root coverage procedures in the treatment of cases with poor prognosis, owing to its pedicled vascularity. PBFP may be considered as a reliable modality for root coverage of such severe maxillary posterior GR defects, as reported, that could not be repaired by other conventional procedures.